Jurisprudential Rulings on the Transformation of Gelatin - Junaid Akbar; Khan, Tasnifullah (Journal of Islamic and Religious Studies, 2016)
Gelatin is derived from Collagen which is a natural protein in the animal’s skin and tissues like cows and pigs. So in this connection there is a doubt in its status that whether it is lawful (Halãl) or unlawful (Harãm). There are two different views about Gelatin. According to the 3rd Fiqhi Conference held in Makka al Mukarma that such Gelatin which has been derived from the Pig tissues and skin is not permissible. On the other side Islamic Fiqha Academy, India has decided that all kind of Gelatin is permissible because of Istihala i.e. its change from one thing into another thing in the light of the views of Imam Muhammad bin Hassan Alshibani in Raddul Muhtar Aala Durrul Mukhtar.